CONSUMER BEHAVIOR ACROSS BORDERS: ARE GLOBAL CONSUMERS REALLY CONVERGING? (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates whether global consumers are genuinely converging in their behaviour or whether enduring cultural differences continue to shape consumption patterns across international markets. Drawing on a systematic review of theoretical and empirical literature within the convergence–divergence paradigm, the study argues that neither convergence nor divergence alone adequately explains contemporary consumer dynamics. While globalisation, digitalization, and the spread of multinational brands have produced measurable similarities in observable consumption patterns – particularly among younger, urban, and digitally connected populations – deeper cultural values, motivations, and decision-making processes remain persistently divergent. The analysis reveals a hybrid model of global consumer behaviour, characterised by surface-level convergence alongside deep-level cultural divergence. The findings carry significant implications for international marketing strategy, specifically supporting a “glocalisation” approach that combines global standardisation with culturally sensitive local adaptation.
Keywords: consumer behaviour; globalisation; convergence; divergence; cultural values; international marketing; glocalisation; cross-cultural consumption